Lateral Force and EMG Activity in Wide- and Narrow-Grip Bench Press in Various Conditions - Michiya Tanimoto; Hiroshi Arakawa; Mauto Sato; Akinori Nagano (MDPI AG, 2023)
The purpose of this study was to investigate the lateral force and contribution of shoulder horizontal adductor and elbow extensor muscles activity during wide- and narrow-grip bench press (BP) in various conditions, such as resistance-trained/non-trained, concentric/eccentric, and muscle fatigue/non-fatigue. We measured the lateral force on the bar and the electromyographic (EMG) muscle activity of pectoralis major (PM) and triceps brachii (TB) during 10 RM BP with wide grip (81 cm) and narrow grip (40 cm) in seven resistance-trained men and seven non-trained men. The all-reps average of the lateral-to-vertical force ratio both in resistance-trained and non-trained subjects was about 30% outward for the wide grip and about 10% inward for the narrow grip. The EMG contribution ratio PM/TB shows no significant differences between narrow and wide grip in all evaluated conditions except in non-trained subjects' muscle fatigue eccentric phase. Both resistance-trained and non-trained subjects did not push the bar straight upward, and the EMG PM/TB was almost unchanged by hand width. The direction adjustment of the force on the bar that achieves almost the same muscle activity degree of the shoulder and elbow joints might be optimal BP kinetics.